Unacceptable Forms of Work in the Thai Sex and Entertainment Industry - Villar, Leo Bernardo (Anti-Trafficking Review, 2019)
This article examines the working conditions in sex and entertainment work in Thailand using the Unacceptable Forms of Work (UFW) Framework. Criminalisation of sex work and insufficient oversight of labour conditions increase the vulnerability of sex workers to police harassment; prevent sex workers from accessing legal and social protections; and contribute to the decent work deficit in the sector. Protecting the human rights of sex workers and ensuring decent work in the Thai sex and entertainment industry necessarily involves the decriminalisation of sex work; amending labour and social protection laws, policies, and systems to be inclusive of sex workers; and ensuring implementation. Throughout the process of policy change, the involvement of sex workers, their employers, and civil society organisations is crucial.